في الفئران المختبرية ودراسة التغيرات النسجية المصاحبة لها Echinococcus granulosus استزراع الاكياس العدرية لطفيلي المشوكة الحبيبية - عبد الامير عزيز الحلفي عذراء (University of Thi-Qar Journal of Science, 2010)
This study was carried out to follow liability of transporting hydatid cyst among mice , Cysts isolated from mice labture infected by protoscolex after four month ,and then surgically transpored to uninfected mice. After one month post cultivation the cyst forming two laminated layer ,one of this developed and the other is still in the beginning of development in addition to germinal layer which consist of more row of cells, Control animals had cysts formed from one laminated layer and one row of germ layer.The histological changes in cultivated animals were less sever than animals infected withprotoscolex